Forecasting Unemployment in North Sumatra Using Double Exponential Smoothing Method. Issue 1 (February 2021) - Syafwan, Havid; Syafwan, Mahdhivan; Syafwan, Elvathna; Hadi, Aulia Fitrul; Putri, Pristiyanilicia
Abstract: The reseach aims to predict the unemployment in the province of North Sumatra in 2020 using the Double Exponential Smoothing (DES) method. The data used is derived from the Central Agency Statistik (BPS) of North Sumatra province where the actual data is taken within 20 years from 2000 to 2019. The accuracy method in this research uses MAD to count the number of errors, MSE to evaluate forecasting methods, and MAPE to calculate the percentage of errors. Results of this research in the form of forecasting the number of unemployment in North Sumatra in 2020 that is 381459 people in the value of alpha 0.6 with a MAD value of 77402.12, MSE value of 12524690448.31, and MAPE value of 16.35%.